Feed Intake, Growth Performance and Nutrient Digestibility of Broiler Chicks Fed Diets Containing Varying Levels of Sorghum Dried Brewers’ Grains - Adama, T.Z.; Ogunbajo, S.A.; Mambo, M. (International Journal of Poultry Science, 2007)
Three hundred Dako broiler chicks of both sexes each having average initial weight of 86.4 g were randomly distributed into five treatments with two replicates each with 30 birds. Five iso-nitrogenous and iso-caloric starter and finisher diets were formulated and fed for a period of four weeks at starter and finisher phases. Sorghum Dried Brewer’s Grain (SDBG) was used at the levels of 0% (control), 10%, 20%, 30% and 40% to replace maize grain and groundnut cake (GNC) in the diets at both starter and finisher phases. Feed intake, growth performance of the birds as well as the digestibility coefficients and the gross margins of the diets were measured. Digestibility values were not significantly affected up to a level of 20% SDBG in the diet. Also, cost of feed/kg declined with increasing levels of SDBG. Gross margin was highest at SDBG level of 20%. It was concluded that SDBG inclusion at a level of 20% in broiler diets will reduce the cost of feed and increase profit margin.